Proteomics detection of S100A6 in tumor tissue interstitial fluid and evaluation of its potential as a biomarker of cholangiocarcinoma - Sudarat Onsurathum; Ornuma Haonon; Porntip Pinlaor; Chawalit Pairojkul; Narong Khuntikeo; Raynoo Thanan; Sittiruk Roytrakul; Somchai Pinlaor (Tumor Biology, 2018)
Tumor interstitial fluid contains tumor-specific proteins that may be useful biomarkers for cancers. In this study, we identified proteins present in cholangiocarcinoma interstitial fluid. Proteins derived from three samples of tumor interstitial fluid and paired samples of adjacent normal interstitial fluid from cholangiocarcinoma patients were subjected to two-dimensional liquid chromatography with tandem mass spectrometry. Candidate proteins were selected based on a greater than twofold change in expression levels between tumor interstitial fluid and normal interstitial fluid. Upregulation of six proteins in tumor interstitial fluid, including S100 calcium binding protein A6 (S100A6), S100 calcium binding protein A9, aldo-keto reductase family 1 member C4, neuropilin-1, 14-3-3 zeta/delta, and triosephosphate isomerase was assessed by western blot and immunohistochemistry. Their potential as markers was evaluated in human cholangiocarcinoma tissue arrays, and in serum using enzyme-linked immunosorbent assay. Expression of S100A6 was higher in tumor interstitial fluid than in normal interstitial fluid and showed the highest positive rate (98.96%) in cholangiocarcinoma tissues. Serum levels of S100A6 did not differ between cholangitis and cholangiocarcinoma patients, but were significantly higher than in healthy individuals ( p  < 0.0001). In cholangiocarcinoma cases, S100A6 level was associated with vascular invasion ( p  = 0.007) and could distinguish cholangiocarcinoma patients from healthy individuals as effectively as the carbohydrate antigen 19-9. In addition, potential for drug treatment targeting S100A6 and other candidate proteins was also demonstrated using STITCH analysis. In conclusion, proteomics analysis of tumor interstitial fluid could be a new approach for biomarker discovery, and S100A6 is a potential risk marker for screening of cholangiocarcinoma.